Solve each radical equation. square root 5x^2-3x=2x

1 answer

sqrt(5x^2 - 3x) = 2x
First thing to do is to square both sides of the equation, then solve for x:
[sqrt(5x^2 - 3x)]^2 = (2x)^2
5x^2 - 3x = 4x^2
x^2 - 3x = 0
x(x - 3) = 0
x = 0
x = 3
Then to check if it really satisfies the original equation, substitute the x values back to the original:
x = 0:
sqrt(5(0)^2 - 3(0)) = 2(0)
sqrt(0 - 0) = 0
0 = 0
Thus x is indeed equal to 0.

x = 3:
sqrt(5(3)^2 - 3(3)) = 2(3)
sqrt(45 - 9) = 6
sqrt(36) = 6
6 = 6
Thus x is indeed equal to 3.

Hope this helps~ :3
Similar Questions
    1. answers icon 16 answers
  1. Express in simplest radical form.square root of, 3, x, end square root 3x ​ Answer Multiple Choice Answers square root of, 3,
    1. answers icon 1 answer
  2. Ok so I'm suppose to do thisSquare root of 6 ___________________ Square root of 2 I know when you divide a radical over radical
    1. answers icon 1 answer
  3. Use the quadratic formula to solve the equation. Give exact answers:2x^2 -1 = 6x. The choices are: a) -3 + square root(7)/2, -3
    1. answers icon 4 answers
more similar questions